Multi-layer 2D grain structure simulation in selective laser melting of stainless steel 316L - Yeong, Wai Yee (2018)
Additive manufacturing (AM) of metals allows high customization and offers manufacturing with greater geometrical freedom. Performance of metals is highly dependent on the microstructure, while the formation of microstructures in printed metal parts depends largely on the process parameters. Numerical studies of AM processes provide insights on the processing parameters and the thermal interaction between energy source and the material. In this article, grain structure of selective laser melted part was investigated using cellular automata and finite element method. Finite element method was used to obtain the temperature history of metal powders and substrate. Thereafter, the temperature history was input to a cellular automata model to simulate the formation of grain structure and grain angles. The models were simulated in 2D and for multiple build layers. Two cases with different scanning speeds were investigated while the energy density was kept constant. The size and angles of grains were investigated. It was found that competitive growth happen in the first two layers and little change in grains happen after the third layer. The shorter melt pool lead to coarser grains and lower fraction of high angle grain boundaries (HAGB). While the longer melt pool lead to finger grains and higher fraction of HAGB.